Allogeneic hematopoietic stem cell transplantation for nonmalignant hematologic disorders using chemotherapy-only cytoreductive regimens and T-cell-depleted grafts from human leukocyte antigen–matched or –mismatched donors. (17th August 2016) - Mussetti, Alberto; Kernan, Nancy A.; Prockop, Susan E; Scaradavou, Andromachi; Lehrman, Rachel; Ruggiero, Julianne M; Curran, Kevin; Kobos, Rachel; O'Reilly, Richard; Boulad, Farid
ABSTRACT: Nonmalignant hematologic disorders (NMHD) of childhood comprise a variety of disorders, including acquired severe aplastic anemia and inherited marrow failure syndromes. Patients with high-risk NMHD without matched related donors fare poorly with allogeneic hematopoietic alternative donor stem cell transplantation (allo-HSCT) and are at high risk for developing graft-versus-host disease following unmodified grafts. The authors retrospectively analyzed data on 18 patients affected by NMHD, lacking a human leukocyte antigen (HLA)-identical sibling donor, who underwent an alternative donor allo-HSCT at their institution between April 2005 and May 2013. Fifty percent of the patients had received prior immunosuppressive therapy, 72% had a history of infections, and 56% were transfusion dependent at the time of transplant. Cytoreduction included a combination of 3 of 5 agents: fludarabine, melphalan, thiotepa, busulfan, and cyclophosphamide. Grafts were T-cell depleted. All evaluable patients engrafted. Five died of transplant complications. The cumulative incidence of graft-versus-host disease was 6%. No patient had recurrence of disease. Five-year overall survival was 77%. Age at transplant <6 years was strongly associated with better survival. Based on these results, transplant with chemotherapy-only cytoreductive regimens and T-cell-depleted stem cell transplants could be recommended for patients with high-risk NMHD, especially at a younger age.